(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Chumak A. The organization of creative activities in the classroom technology as a method of forming kompetetntnoy individual students. In this paper the possibilities of creative activity in classroom technology, aimed at creating a set of skills in students who reveal their capacity for professional, creative activity and life, based on knowledge, values, experience, abilities acquired through training.